Handling of Child Abuse at the Social Affairs, Women’s Empowerment, and Child Protection Office of Banjar Regency - Miradiah, Nova Jumiatul; Amka, Amka; Irwansyah, Irwansyah (International Journal of Multidisciplinary Approach Research and Science, 2025)
This study analyzes the prevention and handling of child abuse in Banjar Regency, emphasizing the role of institutions, social networks, and cultural dynamics that influence the effectiveness of interventions. Employing a descriptive qualitative approach, data were collected through in-depth interviews, document studies, and field observations. The findings indicate that prevention strategies through socialization, education, and institutional capacity-building have increased community awareness, although challenges remain due to cultural resistance that normalizes domestic violence. Case handling is carried out through multi-channel reporting mechanisms, initial assessments, accompaniment, referrals, and social rehabilitation, with the UPTD PPA serving as the central coordinating hub across sectors. Case studies reveal the complexity of interventions, particularly concerning limited human resources, service access disparities, and social stigma. These findings underscore that child protection requires not only formal institutional interventions but also social norm transformation and family environment strengthening to create more adaptive and protective systems.